Bamboo Diversity in the Maluku Islands, Indonesia - Robiah, Yayah; Rosalina, Dewi; Damayanto, I Putu Gede P. (Jurnal Biodjati, 2022)
There is little documentation of bamboo species diversity and distribution in the Maluku Islands of Indonesia. This study aimed to provide information on the diversity and distribution of Maluku’s bamboo species. The research was conducted in March‒April 2021 at the Herbarium Bogoriense (BO), National Research and Innovation Agency. Herbarium specimens of bamboo in BO collected from the Maluku Islands (Provinces of Maluku and North Maluku) were studied alongside online scanned images of herbarium specimens. Bamboo species were re-identified and validated. A literature study was conducted to enrich the data. A distribution map of bamboo species in the Maluku Islands was compiled. Data were analyzed and presented descriptively. We built an identification key for the bamboo species in the Maluku Islands. There are 16 species and eight genera of bamboo in the Maluku Islands: Bambusa glaucophylla, B. maculata, B. multiplex, B. spinosa, B. tuldoides, B. vulgaris, Dendrocalamus asper, Gigantochloa atter, G. robusta, Neololeba amahussana, N. atra, Phyllostachys aurea, Racemobambos ceramica, Schizostachyum brachycladum, S. lima, and Thyrsostachys siamensis. These bamboo species were found across Maluku Province (Buru, Ambon, Seram, Kei Kecil, Kei Besar, Yamdena, and Tanimbar) and North Maluku Province (Ternate, Tidore, Halmahera, Obi, and Sula) at an altitude of 1‒1100 m above sea level in primary and secondary forests, limestone, peatland edges, city parks, and gardens.